The relationships between self-assessed habitual physical activity and non-invasive measures of cardiac autonomic modulation in young healthy volunteers. - Sandercock, G; Hardy-Shepherd, D; Nunan, D; Brodie, D (2008)
Heart rate variability estimates cardiac autonomic modulation, but the relationship between habitual physical activity and heart rate variability remains unclear. The aims of this study were to compare RR-interval and heart rate variability indices in individuals of different habitual physical activity levels, and examine the relationship between habitual physical activity and heart rate variability. Ninety-two healthy volunteers (47 men, 45 women; mean age 23.1 years, s = 2.1) were divided into tertiles according to the Baecke Questionnaire score. Standard heart rate variability indices were derived from 5-min resting RR-interval recordings with paced respiration (0.25 Hz). Between-group differences and the relationship between habitual physical activity and heart rate variability were assessed. More active participants (tertiles 2-3) had longer RR-intervals than those in tertile 1 (P < 0.05). Participants in tertile 2 had higher root mean squared differences of successive normal RR-intervals than those in tertile 1 and a higher standard deviation of normal RR-intervals than those in tertiles 1 and 3. There was a positive linear relationship between habitual activity and RR-interval. Differing RR-interval lengths were found in subgroups of young individuals according to level of habitual physical activity. More active individuals showed resting bradycardia without evidence of enhanced cardiac parasympathetic modulation. The mechanism linking habitual physical activity and RR-interval length appears to be independent of physiological mechanisms that can be measured by heart rate variability.